Transition metal dichalcogenide growth via close proximity precursor supply - COLEMAN, JONATHAN; DUESBERG, GEORG; HALLAM, TOBY; MCEVOY, NIALL; KIM, HYE; BERNER, NINA; LEE, KANGHO (My University, 2015)
Reliable chemical vapour deposition (CVD) of transition metal dichalcogenides (TMDs) is currently a highly pressing research field, as numerous potential applications rely on the production of high quality films on a macroscopic scale. Here, we show the use of liquid phase exfoliated nanosheets and patterned sputter deposited layers as solid precursors for chemical vapour deposition. TMD monolayers were realized using a close proximity precursor supply in a CVD microreactor setup. A model describing the growth mechanism, which is capable of producing TMD monolayers on arbitrary substrates, is presented. Raman spectroscopy, photoluminescence, X-ray photoelectron spectroscopy, atomic force microscopy, transmission electron microscopy, scanning electron microscopy and electrical transport measurements reveal the high quality of the TMD samples produced. Furthermore, through patterning of the precursor supply, we achieve patterned growth of monolayer TMDs in defined locations, which could be adapted for the facile production of electronic device components.
PUBLISHED
Keywords: Reliable chemical vapour deposition (CVD) of transition metal dichalcogenides; Reliable chemical vapour deposition (CVD) of transition metal dichalcogenides